Māori and autism: A scoping review. (October 2021) - Tupou, Jessica; Curtis, Sally; Taare-Smith, Dorothy; Glasgow, Ali; Waddington, Hannah
Cultural groups may vary considerably in their understandings of autism spectrum disorder and approaches to supporting autistic individuals. However, approaches to researching, identifying and managing autism are largely dominated by Western perspectives. This review provides an overview of the literature related to autism and Māori, the indigenous people of Aotearoa/New Zealand. A search of the peer-reviewed and grey literature identified 273 potentially relevant publications, and 13 of these met inclusion criteria. The included publications addressed questions related to Māori understandings of autism, Māori prevalence rates and diagnostic and support services for Māori. Findings suggest broad differences in Māori and Western understandings of autism and slightly higher autism prevalence rates for Māori than for non-Māori New Zealanders. The need for diagnostic and support services that are both effective and culturally appropriate for Māori was also highlighted. These findings are discussed in relation to implications for future research and the provision of services for autistic Māori. Lay abstract: Most current approaches to identifying, researching and managing autism are based on Western views and understandings. However, different cultural groups may understand and approach autism differently. We searched a wide range of websites, academic journals and other sources for published information related to autism and Māori, the indigenous people of Aotearoa/New Zealand. Our search identified 13 publications that addressed questions related to Māori understandings of autism, Māori prevalence rates and diagnostic and support services for Māori. Overall, we found broad differences in Māori and Western understandings of autism and slightly higher autism prevalence rates for Māori than for non-Māori New Zealanders. Findings also highlighted a need for diagnostic and support services that are both effective and culturally appropriate for Māori. We discuss what these findings might mean for future research and the provision of services for Māori with autism.